PENGARUH PENDIDIKAN KESEHATAN REPRODUKSI TERHADAP PERILAKU SEKSUAL AMAN DAN ANGKA KELAHIRAN DI KOTA MEDAN - EKA SAMUEL PARULIAN HUTASOIT (LP2MTBM MAKARIOZ, 2022)
Medan is a city that has a population of around 2,494,512 people in 2022, of which around 598,366 people are residents at a young age. About 9,050 people have been infected with sexually transmitted diseases, and 20,050 people have been infected with non-communicable sexual diseases and the remaining 569,266 people who are not affected by sexually transmitted diseases, both infectious and non-communicable. 29,100 people infected with this sexually transmitted disease are estimated to be unable to maintain reproductive health properly and optimally, where this situation results in deviant sexual behavior and is not safe for reproductive health, as well as the existence of an inappropriate and unstable birth rate, so that the regularity of this birth rate results in the emergence of abortion, and child neglect, because of the culture of shame in Medan City, as well as the inherent customs that make adolescent girls have to maintain reproductive health, genital health and virginity. This study used descriptive analytical method. The population of this study amounted to 29,100 people who experienced reproductive health problems, where reproductive health problems would cause sexual diseases. The population can be categorized as young women in the Medan City area and its surroundings, where the sample taken amounted to 67 residents who experienced reproductive health problems categorized as young women in the Medan City area and its surroundings. The results proved that the number of people who have a low level of reproductive health are residents in the East Medan District area aged in the range of 15-19 years, where the average population who experience reproductive health problems is young women caused by deviant sexual behavior and low understanding of reproductive health education, resulting in a low and unnatural birth rate, due to the presence of contamination of sexual diseases in mother and baby.